Christ’s redemption and giwu: Cultural contextualisation in Pamona, Indonesia - Pieter G.O. Sunkudon; Daud Daud; Juanda Juanda; Yewin Tjandra; Selmita Paranoan (HTS Teologiese Studies/Theological Studies)
This article examines the contextualisation of the concept of Christ’s redemption in Pamona culture in Central Sulawesi, focussing on the practice of giwu as a restorative mechanism against social and ethical transgressions. Giwu serves to restore social balance and relationship with Pue Mpalaburu, the Creator, similar to Christ’s redemption which restores human relationship with God. This research compares the similarities and differences between the two, identifying challenges and opportunities in integrating Christian teachings with giwu practices. With a faithful and global contextualisation approach, the article explores ways to translate and apply the gospel message in the local cultural context, without compromising theological integrity.